2009
DOI: 10.1099/ijs.0.007971-0
|View full text |Cite
|
Sign up to set email alerts
|

Streptomyces hypolithicus sp. nov., isolated from an Antarctic hypolith community

Abstract: As part of an enzyme-screening programme, an actinobacterium, strain HSM#10 T , was isolated from a sample collected from the base of a translucent quartz rock in Miers Valley, eastern Antarctica. The isolate produced branching vegetative mycelium that was characteristic of filamentous actinobacteria. The chemotaxonomic characteristics of the strain suggested that HSM#10 T should be classified as a member of the genus Streptomyces. Furthermore, phylogenetic analysis based on 16S rRNA gene sequences showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…possess high adaptive capability for surviving in many extreme environmental conditions and their incidence had been documented in diverse extreme habitats including frozen soils, deserts, oceans, Arctic and Antarctic regions ( Maldonado et al, 2008 ; Le Roes-Hill et al, 2009 ; Malviya et al, 2009 ; Okoro et al, 2009 ; Ramesh and Mathivanan, 2009 ; Verma et al, 2009 ; Ivanova et al, 2010 ; Zothanpuia et al, 2018 ). Studies in frozen soils, Arctic and Antarctic regions had revealed a great diversity of cultivable Streptomyces species ( Le Roes-Hill et al, 2009 ; Ivanova et al, 2010 ; Li et al, 2011 ; Zhang et al, 2016b ; Kamjam et al, 2019 ), while in marine and deserts, Streptomyces spp. had been reported as one of the dominant culturable genera ( Okoro et al, 2009 ; Prieto-Davo et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…possess high adaptive capability for surviving in many extreme environmental conditions and their incidence had been documented in diverse extreme habitats including frozen soils, deserts, oceans, Arctic and Antarctic regions ( Maldonado et al, 2008 ; Le Roes-Hill et al, 2009 ; Malviya et al, 2009 ; Okoro et al, 2009 ; Ramesh and Mathivanan, 2009 ; Verma et al, 2009 ; Ivanova et al, 2010 ; Zothanpuia et al, 2018 ). Studies in frozen soils, Arctic and Antarctic regions had revealed a great diversity of cultivable Streptomyces species ( Le Roes-Hill et al, 2009 ; Ivanova et al, 2010 ; Li et al, 2011 ; Zhang et al, 2016b ; Kamjam et al, 2019 ), while in marine and deserts, Streptomyces spp. had been reported as one of the dominant culturable genera ( Okoro et al, 2009 ; Prieto-Davo et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hypolithic communities may also harbour heterotrophic taxa with novel phenotypic traits (e.g. Le Roes‐Hill et al ., 2009). As a result, there is significant opportunity for physiological studies to improve our understanding of hypolithic taxa.…”
Section: Physiological Challengesmentioning
confidence: 99%
“…Tiwari and Gupta (2012) had reviewed on the bioactive compounds reported from different genera of rare Actinomycetes isolated from various natural habitats and conclude that many of the successful antimicrobial agents currently available on the market are produced by rare Actinomycetes. The effort of isolating rare Actinobacteria is now gaining more attention and successful isolations of numerous new taxa of Actinobacteria from Antarctic were reported, such as new species of Nocardiopsis , Micromonospora, Streptomyces and new the genera Friedmanniella and Barrientosiimonas (Yassin et al 1993;Schumann et al 1997;Hirsch et al 2004;Le Roes-Hill et al 2009;Li et al 2011;Lee et al 2013). Low sequence similarity of 16S rRNA gene and distant phyletic lineage from the closest relative type strain showed by the rare Actinobacteria isolates in this study had assigned them to be putative new species of Actinobacteria.…”
Section: Discussionmentioning
confidence: 56%